Bluetooth Technology (International Journal of Engineering and Computer Science, 2017)
Bluetooth technology unplugs our digital peripherals. In short, it is a wireless replacement for many of the cables we currently use to transmit voice and data signals. Bluetooth radio modules use Gaussian Frequency Shift Keying (GFSK) for modulation. Bluetooth employs an FHSS spreading technique, changing frequencies at a rate of 1600 times per second - 160 times the rate at which a wireless LAN changes frequencies. This paper focuses on the attacks and security issues in Bluetooth technology.